Facilitating the grotesque reception and human-nature interrelationship in Tunku Halim's Dark Demon Rising - Ahmad Jafni, Nur Fatin Syuhada; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (Penerbit Universiti Kebangsaan Malaysia, 2016)
Horror novels often celebrate gore, darkness, madness and emotional repression as the central themes to invoke terror and horror in readers. In the novel Dark Demon Rising (1997) the elements of grotesque and nature provide the impetus and the plot, thus invoking horror. Apart from the evident elements of grotesque, nature as a backdrop is also significant. Both elements are omnipresent and pivotal in developing the plot. Noting the relationship between the two elements, this paper explores the relationship between the grotesque and nature through the portrayal of human-nature interconnectedness in the selected novels. This paper utilises the concepts of ecocriticism and grotesque. Ecocriticism provides sufficient explanation on the relationship between humans and the natural world. The concept of grotesque by Wolfgang Kayser provides a solid framework in highlighting and exploring the texts. The application of these concepts will then demonstrate that apart from imagery, the role of nature is also evident in channelling the relationship between human and nature. The interrelationship between nature and the grotesque is portrayed under Kayser’s notion of the grotesque reception. Pertaining to this notion, the interconnectedness is unveiled through the comic/horror and attractive/repulsive dualities. The finding concludes that the element of nature depicts the grotesque reception via the characters’ demeanour, especially the protagonists’ emotions, perceptions and attitude.